Integrate(1+x)/((1-x^2)(2x+1)) with respect to x.

To simplify the fraction first notice (1-x2) = (1-x)(1+x) so the common factor of (1+x) in the numerator and denominator can be cancelled. (1+x)/((1-x^2)(2x+1)) = 1/((1-x)(2x+1)), then we need to split this fractions into partials. 1/((1-x)(2x+1)) = A/(1-x) + B/(2x+1) which implies 1 = A(2x+1) + B(1-x). Setting x = 1, 1 = 3A so A = 1/3. Setting x = -1/2, 1 = 3B/2 so B = 2/3. So we must integrate (1/3(1-x) + 2/3(2x+1)), the integral of 2/3(2x+1) is (ln|2x+1|)/3 since the numerator is one third of the derivative of the denominator. Similarly the integral of 1/3(1-x) is (-ln|1-x|)/3. So the answer is (ln|2x+1| - ln|1-x|)/3 + c

Answered by Ravinder H. Maths tutor

3163 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

How does a hypothesis test work?


Differentiate the function f(x) = sin(x)/(x^2 +1) , giving your answer in the form of a single fraction. Is x=0 a stationary point of this curve?


Integrate ln(x)


Integrate xsin(x) with respect to x


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences